Probability to Apply for The Pre-Employment Card Program During the Covid-19 Pandemic in NTB Province - Yassinta Ben Katarti Latiffa Dinar (Jurnal Ekonomi Dan Statistik Indonesia, 2022)
The pre-employment card program is initiate to deal with the impact of the pandemic on the labor force. We conducted this study to see what factors have the probability of influencing a person's decision to apply for the pre-employment card program in NTB Province during the pandemic. The analytical method used is binary logistic regression. The August 2020 National Labor Force Survey data from the Statistics of NTB Province was processed to answer the purpose of the analysis. The result shows that four factors in the model influence the labor force in NTB Province's decision to sign up for the pre-employment card program. Those factors are graduating from school in the last year, previous work experience, not working due to covid, and the length of looking for a job.